Leaf Photosynthetic Parameters Vcmax and Jmax and Supporting Gas Exchange Data, Barrow, Alaska, 2012-2016 - Alistair Rogers; Kim Ely; Shawn Serbin (ESS-DIVE: Deep Insight for Earth Science Data, 2017)
Photosynthetic parameters Vcmax and Jmax estimated from CO2 response curves and from light saturated photosynthesis using the one point method. Data were collected in Barrow 2012-2016 on 7 species - Arctophila fulva, Arctagrostis latifolia, Carex aquatilis, Dupontia fisheri, Eriophorum angustifolium, Petasites frigidus, Salix pulchra. To allow for future reanalysis of our data, and to maximize further use of it by the modelling community, all our data including our raw gas exchange data is available. This dataset contains 3 csv, 3 xlsx, and 1 pdf files. The Next-Generation Ecosystem Experiments: Arctic (NGEE Arctic), was a research effort to reduce uncertainty in Earth System Models by developing a predictive understanding of carbon-rich Arctic ecosystems and feedbacks to climate. NGEE Arctic was supported by the Department of Energy's Office of Biological and Environmental Research. The NGEE Arctic project had two field research sites: 1) located within the Arctic polygonal tundra coastal region on the Barrow Environmental Observatory (BEO) and the North Slope near Utqiagvik (Barrow), Alaska and 2) multiple areas on the discontinuous permafrost region of the Seward Peninsula north of Nome, Alaska. Through observations, experiments, and synthesis with existing datasets, NGEE Arctic provided an enhanced knowledge base for multi-scale modeling and contributed to improved process representation at global pan-Arctic scales within the Department of Energy's Earth system Model (the Energy Exascale Earth System Model, or E3SM), and specifically within the E3SM Land Model component (ELM).